Display agent of SA-508Gr.3 steel for nuclear power and application of display agent
By using aqueous sodium chloride solution for electrolytic display, the problem of the difficulty in displaying the complex structure and austenite grain boundaries of SA-508Gr.3 steel for nuclear power is solved, and clear and true tissue display and grain size assessment are achieved, avoiding safety hazards and environmental pollution.
Patent Information
- Application Number
- CN202411516397.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to clearly display the tempered martensite, tempered bainite structure or complex structure of tempered martensite plus tempered bainite and austenite grain boundaries of SA-508Gr.3 steel for nuclear power, resulting in the inability to achieve grain size assessment.
Using aqueous sodium chloride solution as the display agent, an oxidation reaction occurred on the anode by electrolysis, showing the complex structure of tempered martensite, tempered bainite structure or tempered martensite plus tempered bainite and austenite grain boundary of SA-508Gr.3 steel.
It realizes a clear and complete display of the complex structure and austenite grain boundaries of SA-508Gr.3 steel, ensuring the authenticity of the grain size assessment results, and avoiding safety hazards and environmental pollution of traditional chemical corrosion methods.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic detection, in particular to a display agent of SA-508Gr.3 steel for nuclear power and application thereof. Background Art
[0002] SA-508Gr.3 for nuclear power is an ASME grade. The comprehensive mechanical properties of nuclear power forgings made of it depend largely on its heat treatment process and corresponding microstructure. Its final performance heat treatment adopts quenching and tempering heat treatment (i.e. quenching + high temperature tempering treatment) to obtain tempered martensite, tempered bainite structure or tempered martensite plus tempered bainite complex structure with a grain size of 5 or finer, thus having excellent comprehensive mechanical properties. The standard usually requires the measurement of austenite grain size, but to measure the grain size, the austenite grain boundary must be displayed first. However, for the complex structure of tempered martensite, tempered bainite or tempered martensite plus tempered bainite of SA-508Gr.3 for nuclear power after quenching and tempering, its austenite grain boundary is difficult to display with general corrosives (such as 4% nitric acid alcohol solution). How to display the austenite grain boundary without distortion has always been a difficulty.
[0003] At present, the display agents for displaying tempered martensite, tempered bainite or tempered martensite plus tempered bainite and complex structures and grain boundaries in the industry are picric acid aqueous solution reagents and nitric acid alcohol acid; picric acid is a kind of explosive, bitter, and highly explosive. It has been listed as an explosive and dangerous drug by the state, and its production and sales are strictly controlled and cannot be purchased; nitric acid alcohol has a very poor effect and can only display the approximate structure morphology within the crystal, but cannot display the austenite grain boundary. The evaluation of grain size cannot be achieved, which brings hidden dangers to the subsequent production and safe use of parts.
[0004] The existing methods for displaying the complex organization and grain size of tempered martensite, tempered bainite, or tempered martensite plus tempered bainite of SA-508Gr.3 steel for nuclear power are mainly traditional chemical corrosion methods. Chemical corrosion display methods such as picric acid aqueous solution and nitric acid alcohol can only display the approximate organization morphology within the crystal, but cannot display the austenite grain boundary, and the effect is very poor. Among them, picric acid has been listed as an explosive and dangerous drug by the state, and its production and sales are strictly controlled and cannot be purchased; and commonly used display agents such as nitric acid alcohol use strong acids, which are also harmful to the environment and operators. It is difficult for the existing technologies to clearly display the complex organization and austenite grain boundary of tempered martensite, tempered bainite, or tempered martensite plus tempered bainite, making it impossible to evaluate the grain size. Summary of the invention
[0005] In view of the above problems, the present invention provides an indicator of SA-508Gr.3 steel for nuclear power. The indicator can be used to obtain clear and complete complex structures and austenite grain boundaries of tempered martensite and / or tempered bainite structures of SA-508Gr.3 steel by electrolysis, and the austenite grain size assessment result is true and effective.
[0006] In order to achieve the above object, the present invention provides a display agent for SA-508Gr.3 steel for nuclear power, which consists of sodium chloride and a solvent.
[0007] In the process of studying the above technical problems, the inventors found that the main reason why it is difficult to clearly display the tempered martensite, tempered bainite structure or the complex structure of tempered martensite plus tempered bainite and austenite grain boundaries of SA-508Gr.3 steel is that the interface energy of the original austenite grain boundary is usually higher than the interface energy of the tempered precipitation phase and microscopic substructure in the crystal. The use of general corrosive agents (such as 4% nitric acid alcohol solution) through chemical corrosion will make the interior of the grain susceptible to corrosion and display its microstructure. Sodium chloride, as an inorganic ionic compound, has the chemical formula NaCl, white non-toxic cubic crystals or white crystalline powder, odorless, salty taste, is the main component of table salt, and is harmless to the environment and inspectors. It is easily soluble in water, and its aqueous solution is neutral. Sodium chloride has good stability, and its aqueous solution is a strong electrolyte. Therefore, the inventor proposes to use NaCl aqueous solution as an active ion conductor electrolyte, and preferentially corrode the grain boundaries by ionizing the Cl ions in NaCl, and an oxidation reaction occurs on the metal block-like interface as the anode, thereby showing the tempered martensite, tempered bainite structure or the complex structure of tempered martensite plus tempered bainite and austenite grain boundaries of SA-508Gr.3 steel, with good reproducibility. In addition, the above-mentioned display agent has a simple formula, easy-to-obtain materials, a neutral pH value, and is non-corrosive. It replaces the acidic solution in the conventional chemical corrosion method, does not cause safety hazards to the operator, and the residual liquid after use does not need to be specially recovered and processed, which solves the problems of residual liquid processing and environmental pollution, and avoids the problems of picric acid being toxic, harmful, and difficult to purchase. The above-mentioned display agent has been used in detection with good results; the use results show that the tempered martensite, tempered bainite structure or the complex structure of tempered martensite plus tempered bainite and austenite grain boundaries of SA-508Gr.3 steel can be obtained clearly and completely, and the austenite grain size evaluation result is true and effective.
[0008] In one embodiment, the display agent is composed of the following raw materials in percentage by weight: Sodium chloride 15%-20% Solvent Residue.
[0009] In one embodiment, the solvent has a neutral acidity.
[0010] In one embodiment, the solvent comprises water.
[0011] The present invention also provides application of the display agent in metallographic detection of SA-508Gr.3 steel for nuclear power.
[0012] The present invention also provides a metallographic detection method, which comprises the following steps: pre-treating the sample to be detected to obtain a detection surface, electrolyzing the sample to be detected using the display agent, washing and drying the sample to be detected.
[0013] The above metallographic detection method solves the problem that the complex structure and austenite grain boundary of SA-508Gr.3 steel for nuclear power are difficult to display by electrolyzing SA-508Gr.3 steel with a specific display agent, such as tempered martensite, tempered bainite, or tempered martensite plus tempered bainite. The sample to be tested after drying can be observed and imaged under a metallographic microscope for organization evaluation and austenite grain size measurement. The austenite grain size can be evaluated according to the actual situation by using the comparison method, intercept method, area method, etc. required by the standard. The grain size results obtained by multiple experimental tests by different operators are consistent, which can prove that the evaluation results are true and valid; the displayed organizational morphology is true and complete, and the austenite grain boundary is clearly visible. The present invention can clearly and completely display the organization and austenite grain boundaries, has a clean and environmentally friendly formula, consumes less materials, and does not have any potential safety hazards. Compared with the existing chemical corrosion technology, it can accurately evaluate the austenite grain size of SA-508Gr.3 forgings tempered martensite, tempered bainite organization or tempered martensite plus tempered bainite complex organization In one embodiment, the pretreatment includes grinding, polishing and washing.
[0014] In one embodiment, the electrolysis conditions include: voltage of 7-9V, current of 1-2A, temperature of 25-30°C, and electrolysis time of 10-20s.
[0015] In one embodiment, the anode of the electrolysis is a sample to be tested, and the cathode of the electrolysis is a stainless steel plate.
[0016] In one embodiment, the sample to be tested is SA-508Gr.3 steel for nuclear power.
[0017] In one embodiment, the sample to be tested includes tempered martensite and / or tempered bainite of SA-508Gr.3 steel for nuclear power.
[0018] The present invention also provides application of the metallographic detection method in metallographic detection of SA-508Gr.3 steel for nuclear power.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses an indicator for SA-508Gr.3 steel for nuclear power and its application. The indicator can be used to obtain the complex structure and austenite grain boundary of tempered martensite and / or tempered bainite structure of SA-508Gr.3 steel clearly and completely by electrolysis, and the austenite grain size evaluation result is authentic and effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The microstructure and austenite grain boundary morphology of the SA-508Gr.3Cl.1 steel electrolyzed in 15% NaCl aqueous solution 7V, 1A of Example 1 (400X); Figure 2 The microstructure and austenite grain boundary morphology of the SA-508Gr.3Cl.1 steel electrolyzed in 15% NaCl aqueous solution 8V, 1A of Example 2 (400X); Figure 3 The microstructure and austenite grain boundary morphology of the SA-508Gr.3Cl.1 steel electrolyzed in 20% NaCl aqueous solution 9V, 2A of Example 3 (400X); Figure 4 The microstructure of SA-508Gr.3Cl.1 steel wiped with 4% HNO3 alcohol in Comparative Example 1 (400X); Figure 5 The microstructure of SA-508Gr.3Cl.1 steel electrolyzed in 15% KCl aqueous solution at 8V and 1A in Comparative Example 2 (400X); Figure 6 This is the microstructure morphology (400X) of SA-508Gr.3Cl.1 steel electrolyzed in 15% NaCl aqueous solution at 10V and 5A in Comparative Example 3. DETAILED DESCRIPTION
[0021] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0023] source: Unless otherwise specified, the materials and parts used in this embodiment are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.
[0024] Example 1 A metallographic detection method for SA-508Gr.3 steel for nuclear power.
[0025] The sample to be tested was pretreated to obtain a test surface: the material was a SA-508Gr.3Cl.1 steel quenched and tempered sample, the test surface was coarsely ground and finely ground with abrasive paper in sequence, then mechanically polished with diamond spray, and then cleaned with anhydrous ethanol to obtain a test surface.
[0026] Electrolysis, washing and drying: Pour the prepared 15% mass percentage concentration NaCl aqueous solution (weigh 15g NaCl (analytical grade) and 85g distilled water, pour NaCl and distilled water into a glass container in turn and stir evenly with a glass rod) into the electrolytic cell; use the ground and polished sample as the anode and the stainless plate as the cathode, the voltage is 7V, the current is 1A, and the room temperature. After electrolysis for 20s, take out the sample, rinse it with clean water, drop anhydrous ethanol on it and blow it dry with hot air.
[0027] The prepared samples were observed and images were collected under a metallographic microscope. The quenched and tempered structure of SA-508Gr.3Cl.1 steel is tempered martensite plus tempered bainite. The structure is real and complete, and the austenite grain boundary is clearly visible. The grain size is measured by the intercept method, which is level 7, the area method, which is level 7, and the comparison method, which is level 7. Figure 1 .
[0028] Example 2 A metallographic detection method for SA-508Gr.3 steel for nuclear power.
[0029] The sample to be tested was pretreated to obtain a test surface: the material was a SA-508Gr.3Cl.1 steel quenched and tempered sample, the test surface was coarsely ground and finely ground with abrasive paper in sequence, then mechanically polished with diamond spray, and then cleaned with anhydrous ethanol to obtain a test surface.
[0030] Electrolysis, washing and drying: Pour the prepared 15% mass percentage concentration NaCl aqueous solution (weigh 15g NaCl (analytical grade) and 85g distilled water, pour NaCl and distilled water into a glass container in turn and stir evenly with a glass rod) into the electrolytic cell; use the ground and polished sample as the anode and the stainless plate as the cathode, the voltage is 8V, the current is 1A, and the room temperature. After electrolysis for 10s, take out the sample, rinse it with clean water, drop anhydrous ethanol on it and blow it dry with hot air.
[0031] The prepared samples were observed and images were collected under a metallographic microscope. The quenched and tempered structure of SA-508Gr.3Cl.1 steel is tempered martensite plus tempered bainite. The structure is real and complete, and the austenite grain boundary is clearly visible. The grain size is measured by the intercept method, which is level 7, the area method, which is level 7, and the comparison method, which is level 7. Figure 2 .
[0032] Example 3 A metallographic detection method for SA-508Gr.3 steel for nuclear power.
[0033] The sample to be tested was pretreated to obtain a test surface: the material was a SA-508Gr.3Cl.1 steel quenched and tempered sample, the test surface was coarsely ground and finely ground with abrasive paper in sequence, then mechanically polished with diamond spray, and then cleaned with anhydrous ethanol to obtain a test surface.
[0034] Electrolysis, washing and drying: Pour the prepared 20% mass percentage concentration of NaCl aqueous solution (weigh 20g NaCl (analytical grade) and 80g distilled water, pour NaCl and distilled water into a glass container in turn and stir evenly with a glass rod) into the electrolytic cell; use the ground and polished sample as the anode and the stainless plate as the cathode, the voltage is 9V, the current is 2A, and the room temperature. After electrolysis for 20s, take out the sample, rinse it with clean water, drop anhydrous ethanol on it and blow it dry with hot air.
[0035] The prepared samples were observed and images were collected under a metallographic microscope. The quenched and tempered structure of SA-508Gr.3Cl.1 steel is tempered martensite plus tempered bainite. The structure is real and complete, and the austenite grain boundary is clearly visible. The grain size is tested by the intercept method and the result is 7, the area method and the comparison method, as shown in Figure 1. Figure 3 .
[0036] Comparative Example 1 The sample to be tested was pretreated to obtain a test surface: the material was a SA-508Gr.3Cl.1 steel quenched and tempered sample, the test surface was coarsely ground and finely ground with abrasive paper in sequence, then mechanically polished with diamond spray, and then cleaned with anhydrous ethanol to obtain a test surface.
[0037] Chemical corrosion, washing and drying: Prepare a 4% HNO3 alcohol solution by volume; soak the absorbent cotton with 4% HNO3 alcohol solution and gently wipe the polished surface of the sample. When the polished surface of the sample turns silver-gray, rinse it with clean water, add anhydrous ethanol and blow dry it with hot air.
[0038] The prepared samples were observed and images were collected under a metallographic microscope. The tempered structure of SA-508Gr.3Cl.1 steel can be vaguely distinguished as tempered martensite and tempered bainite, but the structure morphology is not clear, true and complete enough. The austenite grain boundary is not visible, and the grain size cannot be measured. Figure 4 .
[0039] Comparative Example 2 The sample to be tested was pretreated to obtain a test surface: the material was a SA-508Gr.3Cl.1 steel quenched and tempered sample, the test surface was coarsely ground and finely ground with abrasive paper in sequence, then mechanically polished with diamond spray, and then cleaned with anhydrous ethanol to obtain a test surface.
[0040] Electrolysis, washing and drying: Pour the prepared 15% KCl aqueous solution into the electrolytic cell; use the ground and polished sample as the anode and the stainless plate as the cathode. The voltage is 8V and the current is 1A at room temperature. After electrolysis for 20s, take out the sample, rinse it with clean water, drip anhydrous ethanol on it and blow it dry with hot air.
[0041] The prepared samples were observed and images were collected under a metallographic microscope. The tempered structure of SA-508Gr.3Cl.1 steel can be vaguely distinguished as tempered martensite and tempered bainite, but the structure morphology is not clear, true and complete enough. The austenite grain boundary is not visible, and the grain size cannot be measured. Figure 5 .
[0042] Comparative Example 3 The sample to be tested was pretreated to obtain a test surface: the material was a SA-508Gr.3Cl.1 steel quenched and tempered sample, the test surface was coarsely ground and finely ground with abrasive paper in sequence, then mechanically polished with diamond spray, and then cleaned with anhydrous ethanol to obtain a test surface.
[0043] Electrolysis, washing and drying: Pour the prepared 15% NaCl aqueous solution into the electrolytic cell; use the ground and polished sample as the anode and the stainless plate as the cathode. The voltage is 10V, the current is 5A, and the electrolysis is performed at room temperature for 20s. Then, take out the sample, rinse it with clean water, drip anhydrous ethanol on it and blow it dry with hot air.
[0044] The prepared samples were observed and images were collected under a metallographic microscope. The tempered structure of SA-508Gr.3Cl.1 steel can be vaguely distinguished as tempered martensite and tempered bainite. Pit corrosion pits appeared on the inspection surface, and the structure morphology was not clear, true and complete enough. The austenite grain boundary was vaguely visible, and the grain size could not be measured. Figure 6 .
[0045] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0046] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A display agent for SA-508Gr.3 steel for nuclear power, characterized in that: The developing agent consists of sodium chloride and a solvent.
2. The disclosing agent according to claim 1, characterized in that The display agent is composed of the following raw materials in percentage by mass: Sodium chloride 15%-20% Solvent Residue.
3. The disclosing agent according to claim 1, characterized in that The solvent includes water.
4. Use of the developer according to any one of claims 1 to 3 in metallographic detection of SA-508Gr.3 steel for nuclear power.
5. A metallographic detection method, characterized in that: The following steps are involved: The sample to be tested is pretreated to obtain a detection surface, and the sample to be tested is electrolyzed, washed, and dried using the display agent described in any one of claims 1 to 3.
6. The metallographic detection method according to claim 5, characterized in that: The electrolysis conditions include: voltage of 7-9V, current of 1-2A, temperature of 25-30°C, and electrolysis time of 10-20s.
7. The metallographic detection method according to claim 5, characterized in that: The anode of the electrolysis is the sample to be tested, and the cathode of the electrolysis is a stainless steel plate.
8. The metallographic detection method according to claim 5, characterized in that: The sample to be tested is SA-508Gr.3 steel for nuclear power.
9. The metallographic detection method according to claim 8, characterized in that: The sample to be tested includes tempered martensite and / or tempered bainite of SA-508Gr.3 steel for nuclear power.
10. Application of the metallographic detection method according to any one of claims 5 to 9 in metallographic detection of SA-508Gr.3 steel for nuclear power.
Citation Information
Patent Citations
Method for observing real topography of nonmetallic inclusion in steel
CN101812720A
Method for displaying thermal deformation texture of steel used for nuclear power pressure container
CN102353566A
Metallographic sample preparation method of CrMo steel
CN108760439A
Etching agent for inspecting S31042 and T91 or T92 dissimilar steel welding joint and preparation method of etching agent
CN113310776A
Efficient metallographic electrolytic corrosive agent for hastelloy and detection method
CN115747939A
Cited By
Etching agent and etching method for in-situ microstructure of Mn-Mo-Ni steel for nuclear power
CN121141303A